Hazard Risk Assessment on The Maintenance of Facilities and Infrastructure in ITK Campus Using JSA Method - Mikael Wendy Tulak; Intan Dwi Wahyu; Marita Wulandari; Agung Waskito; Muhammad Ma'arij Harfadli (Jurnal Berkala Kesehatan, 2023)
Applying Occupational Safety and Health culture is very important for workers, including facilities and infrastructure maintenance workers. Facilities and infrastructure maintenance activities at Institut Teknologi Kalimantan have varying levels of risk, ranging from low to high. This study aims to identify and determine the level of work risk, then analyze the risks and hazards of each stage of work and how to control them. This study uses several steps, such as determining the work to be explored, describing the results from the preparatory stage to the implementation of the work, identifying hazards and risks by looking at the severity and likelihood of accidents and occupational diseases occurring in each job, and providing an overview of workplace controls. The analysis results show that the highest risk value is grass cutting at the grass cutting stage using a machine, namely scratches, bruises, and cut legs, with a risk value of 16. This risk is controlled by replacing the blades of the grass cutter, protecting the engine cover, making and implementing Standard Operating Procedure (SOP), and using PPE such as safety shoes.